Osteocyte alterations induce osteoclastogenesis in an in vitro model of gaucher disease - Bondar, Constanza María (2017)
Gaucher disease (GD) is caused by mutations in the glucosylceramidase β (GBA 1) gene that confer a deficient level of activity of glucocerebrosidase (GCase). This deficiency leads to the accumulation of the glycolipid glucocerebroside in the lysosomes of cells, mainly in the monocyte/macrophage lineage. Its mildest form is Type I GD, characterized by non-neuronopathic involvement. Bone compromise is the most disabling aspect of the Gaucher disease. However, the pathophysiological aspects of skeletal alterations are not yet fully understood. The bone tissue homeostasis is maintained by a balance between resorption of old bone by osteoclasts and new bone formation by osteoblasts. A central player in this balance is the osteocyte as it controls both processes. We studied the involvement of osteocytes in an in vitro chemical model of Gaucher disease. The osteocyte cell line MLO-Y4 was exposed to conduritol-β-epoxide (CBE), an inhibitor of GCase, for a period of 7, 14 and 21 days. Conditioned media from CBE-treated osteocytes was found to induce osteoclast differentiation. GCase inhibition caused alterations in Cx43 expression and distribution pattern and an increase in osteocyte apoptosis. Osteoclast differentiation involved osteocyte apoptotic bodies, receptor activator of nuclear factor κ-B ligand (RANKL) and soluble factors. Thus, our results indicate that osteocytes may have a role to play in the bone pathophysiology of GD.